ANALISIS HUBUNGAN FAKTOR PERSONAL KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN AYAM KAMPUNG DI KOTA PADANG - Tevina Edwin; Ida Indrayani; Yolani Utami; Adisti Rastosari (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
This study aims to look at the relationship between personal factors and purchasing decisions for Kampung chicken meat. Because the market is a place for the implementation of the demand and supply processes, it is able to provide products that are in accordance with buyer requests. This research was conducted in Padang city, West Sumatra, to be precise, at the Padang City Market, which is the central market of this area. The research was carried out in September 2022. The sampling technique used was the convenience sampling technique, and the number of samples was 100 people. The research instrument employed closed questionnaires with research variables such as age (X1), education (X2), family size (X3), income (X4), and purchasing decisions (Y). The Spearman rank test was used to analyze data using non-parametric statistical tests. Through the results of the study, it was found that only education had a close relationship with purchasing decisions. Other factors such as age, the number of family members, and income do not have a close relationship with purchasing decisions. The absence of a significant relationship can be influenced by factors outside the factors studied. Keyword : Personality factor, Meat, Kampung Chicken, Padang